"If we're here, it's only because we have no money..." discrimination and violence in Mexican maternity wards - Rosario Valdez Santiago; Luz Arenas Monreal; Anabel Rojas Carmona; Mario Sánchez Domínguez (BMC, 2018)
Abstract Background Structural and gender violence in Mexico take on various forms, obstetric violence among them. The objective of our study consisted in analyzing experiences of structural and gender discrimination against women during childbirth care at two public hospitals in Mexico. Methods We conducted a cross-sectional mixed methods study including a survey of closed questions administered to all women who received health care for vaginal or cesarean childbirth at two public hospitals from May 7 to June 7, 2012 (N = 512). Those who reported some form of abuse on the part of health-care professionals were then invited to complete a semi-structured interview (20 women agreed to participate). In addition, three focus groups were organized with health-care professionals from both institutions (31 participants): two were composed of nurses and one of obstetrician-gynecologists (OB-GYNs). This work deals with the qualitative component of the study. Results The narratives of the health-care professionals interviewed contained expressions of health discrimination relating to certain characteristics of their clients, namely poverty, ignorance, failure to understand instructions and being women. The women, on the other hand, perceived themselves as belonging to a low social class and, as a result, behaved passively with staff throughout their hospital stay. They reported both physical and psychological abuse during care. The first included having their legs manipulated roughly, being strapped to the bed, and being subjected to multiple and careless pelvic examinations. Psychological abuse included reprimands, insults, disrespectful remarks, neglect and scowling gestures when requesting assistance. Conclusions The results of our study bear implications for the doctor-client relationship and for the health system in general. They suggest a need to dismantle medical practice - particularly with regard to obstetrics and gynecology - as it has been historically learned and internalized in Mexico. It is imperative to design public policies and strategies based on targeted interventions for dismantling the multiple forms of structural and gender violence replicated daily by actors in the health system.